Marching song a play - Welles, Orson 1915-1985; Hill, Roger 1895-1990 (Rowman & Littlefield, 2019)
"Marching Song is a play written by Orson Welles and Roger Hill about the abolitionist, John Brown. Welles and Hill collaborated on the play when Welles was seventeen and attending the Todd School for Boys, where Hill was the head schoolmaster"--
Keywords: Brown, John / 1800-1859 / Drama; Abolitionists / United States / Drama; Brown, John / 1800-1859; Abolitionists; United States; Drama; Fiktionale Darstellung